Volcanic eruptions and the global subsea telecommunications network - Michael A. Clare; Isobel A. Yeo; Jacob Nash; James E. Hunt; Semisi Panuve; Alasdair Wilkie; Rebecca Williams; Natasha Dowey; Peter Rowley; Jennifer Barclay; Jeremy Phillips; Jazmin Scarlett; et al. (Bulletin of Volcanology, 2025)
When the first transoceanic telegraph cables were laid in the mid-1800s, rapid communication between continents became possible. The advent of fibre-optic submarine cables in the 1990s catalyzed a global digital revolution. Today, a network of > 1.7 million kilometres of fibre-optic cables crosses the oceans, carrying more than 99% of all digital data traffic worldwide and trillions of dollars in financial transactions. These arteries of the global internet underpin many aspects of our daily lives, and are particularly important for remote island communities that rely on submarine cables for telemedicine, e-commerce, and online education. However, these same remote communities are often in seismically and volcanically active regions and can be prone to natural hazards that threaten their critical subsea communication infrastructure. This vulnerability was acutely exposed in January 2022, when the collapse of the eruption plume of Hunga Volcano triggered fast-moving density currents that damaged Tonga’s only international submarine cable, cutting off an entire nation from global communications in the midst of a volcanic crisis. Here, we present a new comprehensive analysis of damage to subsea communications cables by volcanic events from around the world, and document their diverse impacts. Examples include (i) severing of the telegraph cable crossing the Sunda Strait by a tsunami triggered by the 1883 Krakatau eruption, Indonesia; (ii) ocean-entering pyroclastic density currents, lahars, and landslides during the 1902 eruptions of Mount Pelée, Martinique, that damaged six telegraph cables; (iii) destruction of a cable landing station on Montserrat by a pyroclastic density current in 1997; (iv) submarine slope failure at Kick ‘em Jenny, Grenada, that damaged two fibre-optic cables; (v) complete loss of the telecommunications network due to power outages following the 2000 eruption of Miyake-jima, Japan; and (vi) disruption to subsea cables resulting from the 2021 eruption of La Soufrière, St. Vincent. We find that the causes of damage typically relate to secondary hazards that occur not only at the same time as the eruption climax, but also some time after. There does not appear to be an explosivity intensity threshold for cable-damaging events; however, the extent of damage may be related to the original volcano morphology (e.g. steep slopes), spatial location (e.g. near the coast or partially/totally submerged), the eruption size or explosivity, and/or volcanic depositional processes involved. Based on these diverse case studies, we present lessons learned for enhancing telecommunications resilience, and discuss how subsea cables themselves can be used as sensors to improve understanding and early warning of volcanic hazards, potentially filling a monitoring gap for remote island communities.

The diversity, frequency and severity of natural hazard impacts on subsea telecommunications networks - Lucy Bricheno; Isobel Yeo; Michael Clare; James Hunt; Allan Griffiths; Lionel Carter; Peter J. Talling; Megan Baker; Stuart Wilson; Matthew West; Semisi Panuve; Samuiela Fonua (Earth-Science Reviews, 2024)